The Study on Improving Chinese College Students’ Intercultural Communication Competence in College English Teaching - Cui, Peng (Pacific International Journal, 2022)
Abstract:Intercultural communication competence refers to the ability of people from different cultural backgrounds to come together and communicate.It is also an important skill that college students should possess.However, the college students’ intercultural communication ability is not satisfactory at present.In order to improve college students’ intercultural communication ability at present, this paper puts forward a teaching and training mode to improve students’ intercultural competence under current conditions–the training mode based on English movies, and carries out practical research on this new mode.Finally, this study proves the effectiveness of this new teaching model.